Pengaruh Penggunaan Substrat yang Berbeda Terhadap Pertumbuhan dan Kelangsungan Hidup Larva Rajungan (Portunus pelagicus) - Agus Putra AS; Rini Mastuti; Sorbakti Sinaga (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
Swimming crab is a among Portunidae crab, and in some countries this crab is wellknown as an export commodity. The present study was done to determine the best substrate to improve survival and growth rate of Portunus pelagicus. This study used a completely randomized design with 4 treatments in triplicate. The treatments were: Sand (P1), Mud (P2), Gravel (P3), and Combination of Sand and Gravel (P4). The observed parameters were survival rate, larval weight and length, feed conversion ratio (FCR) and water quality. The results showed that the highest survival rate was seen at P1 (33.67%), the best weight and length gain was at P1 (1.69 g and 0.39 cm) and the lowest was at P2 (1.54 g and 0.34 cm). Data showed that the best FCR is found in treatment P3 of 3.92,.This study showed that the use of sand substrate has the best effect on growth and survival during the rearing of crab larvae.